Looking across north side of Happy River valley, Alaska, August 1914 - University of Washington Libraries. Special Collections Division.
Dotted line drawn on photo shows route. McPherson number: K175 PH Coll 495.1-44c Photograph from album created in circa 1914 by James Lennox McPherson, a civil engineer, that documents the activities of the Kuskokwim Reconnaissance survey party (known as Party No. 11 of the Alaska Railroad Commission expedition). The A.E.C. had assigned McPherson to research the feasibility of building a branch railroad from Anchorage west to the mining districts on the Kuskokwim and Iditarod Rivers.